An Alternative Assessment Model to Improve a Translated Text from Indonesian into English - Tanuwijaya, Marwan; Nugroho, Aditya Cahyo; Ahdi, Pratama; Dewi, Novita (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
The main aspect of translation is how one’s expression in one language is replacedwith an equivalent representation in another language. The representation should beequivalent in terms of its stylistic, referential, and linguistic features. Whether there is a needfor a translation text to be classified as